Opioids Impair Intestinal Epithelial Repair in HIV-Infected Humanized Mice - Meng, Jingjing; Banerjee, Santanu; Zhang, Li; Sindberg, Greg; Moidunny, Shamsudheen; Li, Bin; Robbins, David J.; Girotra, Mohit; Segura, Bradley; Ramakrishnan, Sundaram; Roy, Sabita (Frontiers in Immunology, 2020)
Intestinal barrier dysfunction and subsequent microbial translocation play crucial roles in persistent immune activation leading to HIV disease progression. Opioid use is associated with worse outcome in HIV-infected patients. The exacerbated disease progression by opioids is mainly driven by excessive intestinal inflammation and increased gut permeability. The objective of this study is to investigate how opioids potentiate HIV disease progression by compromising intestinal barrier function and impairing intestinal epithelial self-repair mechanism. In the present study, abnormal intestinal morphology and reduced epithelial proliferation were observed in bone marrow-liver-thymus humanized mice and in HIV-infected patients who were exposed to opioids. In bone marrow-liver-thymus mice, HIV, and morphine independently, and additively induced gut dysbiosis, especially depletion of Lachnospiraceae, Ruminococcaceae, and Muribaculaceae. We also observed that the abundance of Lachnospiraceae, Ruminococcaceae, and Muribaculaceae negatively correlated with apoptosis of epithelial cells, and intestinal IL-6 levels. Previous studies have shown that these bacterial families play crucial roles in maintaining intestinal homeostasis because they include most short-chain fatty acid-producing members. Short-chain fatty acids have been shown to maintain stem cell populations and suppress inflammation in the gut by inhibiting histone deacetylases (HDAC). In addition, we demonstrate that morphine exposure inhibited growth of intestinal organoids derived from HIV transgenic mice by suppressing Notch signaling in an HDAC-dependent manner. These studies implicate an important role for HDAC in intestinal homeostasis and supports HDAC modulation as a therapeutic intervention in improving care of HIV patients, especially in opioid-abusing population.